Comparative study conventional incision and drainage versus primary closure with negative suction drainage of soft tissue abscess - Katamsetti, Siva Sandeep; Bhoir, Lata (International Journal of Research in Medical Sciences, 2024)
Background: An abscess refers to a confined collection of pus within tissues, organs, or specific body spaces, arising from tissue breakdown within the dermal and deeper skin layers. It is a hallmark of infection, identified as an inflammatory lesion containing purulent material, which commonly occurs as a response to a range of biological, chemical, or physical injuries to host tissues. The typical signs of an acute abscess include redness, tenderness, warmth, and swelling, often presenting a fluid-like consistency when pressed. While the overlying epidermis remains intact, the dermis hosts inflammatory cells and degraded tissue. Distinguishing an abscess from similar conditions is essential; erysipelas affects the upper dermis, while cellulitis involves loose connective tissue beneath the dermis, often mimicking an abscess. Methods: This comparative hospital-based study evaluated wound healing time and scarring between two treatment approaches: conventional incision and drainage versus primary closure with a negative suction drain. Fifty patients were randomly divided into two groups: Group A: 25 patients treated with conventional incision and drainage; Group B: 25 patients receiving primary closure with suction drainage following incision and drainage. Results: Primary closure with suction drainage showed faster wound healing, reduced postoperative pain, shorter hospital stays, and a lower recurrence rate compared to the conventional approach. Conclusions: Incorporating primary closure with suction drainage is advantageous over traditional methods, suggesting a need for wider adoption among surgeons as it provides faster recovery, less pain, and improved cosmetic outcomes.